Leia-me como uma história : mulheres e a construção de narrativas da felicidade no Instagram - Severo, Mariana Leoratto (2017)
The present work aims to reflect on feminine happiness narratives in the Instagram application. The object of study is the photographs posted by women in the app. It is understood that contemporary modes of expression overflows ideals of happiness, with women as protagonists. The research is based, mainly, by the contribution of McMahon (2006) and Birman (2010) on happiness; Berger, Luckmann (1966) and Schutz (2008) on narratives and everyday life; Lipovetsky (1997) and Ahmed (2010) on women and Maffesoli (2010) with the method of comprehensive sociology. The theoretical basis is permeated by the idea of performance. In this research, it were revealed five ultrageneralizations that emerged from 250 photographs collected by utilizing the main hashtags of the Instagram app: About the toil of being who you are; About accepting, enjoying and living the moments; About sensuality and self-esteem; About love, affection and being together and about the appreciation of what is beautiful. From this, aspects such as individuality, authenticity, present, moment, hedonism, empowerment, feeling, communion and aestheticization of experience were guides to the understanding of the construction of happiness narratives.